The Epigenetic Regulation of Nonhistone Proteins by SETD7: New Targets in Cancer - Chiang, Chengyao; Yang, Heng; Zhu, Lizhi; Chen, Chunlan; Chen, Cheng; Zuo, You; Zheng, Duo (Frontiers in Genetics, 2022)
Epigenetic modifications are essential mechanism by which to ensure cell homeostasis. One such modification is lysine methylation of nonhistone proteins by SETD7, a mono-methyltransferase containing SET domains. SETD7 methylates over 30 proteins and is thus involved in various classical pathways. As such, SETD7 has been implicated in both the basic functions of normal tissues but also in several pathologies, such as cancers. In this review, we summarize the current knowledge of SETD7 substrates, especially transcriptional-related proteins and enzymes, and their putative roles upon SETD7-mediated methylation. We focus on the role of SETD7 in cancer, and speculate on the possible points of intervention and areas for future research.